2018
DOI: 10.1021/acs.oprd.8b00272
|View full text |Cite
|
Sign up to set email alerts
|

Au Core–Pd Shell Bimetallic Nanoparticles Immobilized within Hyper-Cross-Linked Polystyrene for Mechanistic Study of Suzuki Cross-Coupling: Homogeneous or Heterogeneous Catalysis?

Abstract: The synthesis of catalytically active bimetallic Au–Pd nanoparticles stabilized in hyper-cross-linked polystyrene (HPS) for Suzuki cross-coupling of 4-bromoanisole (4-BrAn) and phenylboronic acid is presented. The core–shell structure with a thin (less than 1 nm) Pd shell and a Au core was proven by X-ray diffraction and high-angle annular dark-field scanning transmission electron microscopy combined with energy-dispersive X-ray spectroscopy. More than a 2-fold increase in 4-BrAn conversion was found in compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 57 publications
2
36
0
1
Order By: Relevance
“…Under visible-light irradiation, the photogenerated electrons and holes activate the chloroarene and aryl boronic acid coupling partners, respectively.T he CeO 2 nanoporousm aterial enhances the photoabsorption and chargec arrierg eneration in Au. [416] It should be noted that all heterogeneousp hotocatalysts we discussed here requiret he presence of Pd for accelerating the reaction. [415] By replacing the TiO 2 support with ah yper-cross-linked polystyrene (HPS) material, Kiwi-Minsker et al carriedo ut the light-mediated crosscoupling of bromoarenesa nd aryl boronic acids in the presence of an Au/Pd/HPSp hotocatalyst.…”
Section: Heterogeneous Synergistic and Bimetallic Au Catalysis For Thmentioning
confidence: 97%
“…Under visible-light irradiation, the photogenerated electrons and holes activate the chloroarene and aryl boronic acid coupling partners, respectively.T he CeO 2 nanoporousm aterial enhances the photoabsorption and chargec arrierg eneration in Au. [416] It should be noted that all heterogeneousp hotocatalysts we discussed here requiret he presence of Pd for accelerating the reaction. [415] By replacing the TiO 2 support with ah yper-cross-linked polystyrene (HPS) material, Kiwi-Minsker et al carriedo ut the light-mediated crosscoupling of bromoarenesa nd aryl boronic acids in the presence of an Au/Pd/HPSp hotocatalyst.…”
Section: Heterogeneous Synergistic and Bimetallic Au Catalysis For Thmentioning
confidence: 97%
“…12,23,24 With the help of the strong localized surface plasmon resonance (LSPR) of Au under light irradiation, Au/Pd bimetallic nanoparticles have been proven to be efficient in light harvesting and as catalysts for the Suzuki coupling reaction. [25][26][27] In this regard, several efforts have been devoted to improvement of the activity of heterogeneous AuPdbased TiO 2 catalysts for the visible-light-induced Suzuki coupling reaction. Yan et al reported a well-designed Au-TiO x -Pd photocatalyst that exhibited high performance towards Suzuki-Miyaura reactions under ambient conditions under solar irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,13–16 ] These are afflicted by the loss of activity ascribed to Pd leaching, low reactivity, narrow substrate scope, thermal sensitivity, agglomerate formation, and demand of high temperature and additional base. [ 1,13–19 ] The decrease of Pd by leaching can be attributed by a complex mechanism including pure homogeneous or heterogeneous or both, [ 19–23 ] and the mechanism was systematically illustrated in earlier work. [ 19 ] In the catalytic processes of Suzuki coupling, oxidative addition of aryl halide to Pd 0 NPs generates a Pd II complex, which engages in transmetallation with arylboronic acids (ABAs) to form a diaryl Pd II complex with high probability to be in soluble form.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,13–19 ] The decrease of Pd by leaching can be attributed by a complex mechanism including pure homogeneous or heterogeneous or both, [ 19–23 ] and the mechanism was systematically illustrated in earlier work. [ 19 ] In the catalytic processes of Suzuki coupling, oxidative addition of aryl halide to Pd 0 NPs generates a Pd II complex, which engages in transmetallation with arylboronic acids (ABAs) to form a diaryl Pd II complex with high probability to be in soluble form. The regenerated Pd 0 particles from diaryl Pd II in the final reduction step may be recaptured onto the surface of existing Pd NPs or remain in solution.…”
Section: Introductionmentioning
confidence: 99%